Chatbot Optimization using Sentiment Analysis and Timeline Navigation - Sodré, Wagner da Silva Maciel; Duarte, Julio Cesar (Revista de Informática Teórica e Aplicada, 2023)
A chatbot or conversational agent is a software that can interact or ``chat’’ with a human user using a natural language, like English, for instance. Since the first chatbot developed, many have been created but most of their problems still persist, like providing the right answer to the user and user acceptance itself. Considering such facts, in this work, we present a chatbot-building framework that considers the use of sentiment analysis and tree timelines to provide a better chatbot answer. For instance, as presented in our experiments, the user can be addressed to a human attendant when its sentiment is very negative, or even try another branch of the tree timeline, as an alternative answer, whenever the user sentiment is less negative.